Self-Induced Photogenic Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The characteristics of photogenic self-induced seizures and their treatment by optical filters in a 2-year-old boy with severe myoclonic epilepsy in infancy are reported from the National Epilepsy Center, Shizuoka Higashi Hospital, Japan.